Project-Based Learning to Improve Creative Thinking Skills in Early Childhood - Rahma Hesti Retno Devi; Pascalian Hadi Pradana; Alam Zulkarnain Ali (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Creative thinking skills are essential for every individual, particularly for early childhood, as they form a fundamental basis for children to explore and maximize their potential. However, field research indicates that, on average, childrenâ€™s creative thinking abilities are still underdeveloped. This condition is influenced by a lack of self-confidence, which causes children to feel hesitant or shy about expressing their ideas, as well as limited knowledge that hinders their ability to think creatively. This study aims to improve early childhood creative thinking skills through the implementation of Project-Based Learning (PjBL). The research employed a Classroom Action Research (CAR) design conducted in two cycles, involving 22 children at TAAM Qurâ€™an Bahrusysyifaâ€™ Kindergarten, Lumajang. The results showed that in Cycle I, only 31% of children reached the â€œvery well developedâ€ category, while in Cycle II this percentage increased significantly to 86%. Therefore, it can be concluded that project-based learning is an effective method for improving creative thinking skills in early childhood.